On one Mathematical Model for Dynamics of Propagation and Retention of Heat over New Fibre Insulation Coating (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
In circumstances, when it is important to replace insulation materials with high content of emissions during production it is necessary to create new heat and sound insulation material, which eliminates CO2 emissions, develop its production techniques and technological machinery – raw material chopper, pulp mixer, termopress, dryer chamber, formatting knifes, determine technical control parameters and control equipment, develop mathematical model of the material and calculation methods for design works. It is necessary to design, manufacture and experimentally test the respective technological equipment for insulation production pilot plant. To get exact physical parameters it is necessary design, manufacture and test unique laboratory equipment for determining the properties of insulation material. The mathematical model describing the dynamics of propagation and retention of heat over fibre insulation coating by taking "inner" specificities (graininess and porosity of layered structure of the considered fibre insulation) of heat insulator into account is proposed in the present paper.